1987
DOI: 10.1029/jb092ib10p10170
|View full text |Cite
|
Sign up to set email alerts
|

Local crustal extension at Mount St. Helens, Washington

Abstract: Geophysics Prowlram AK-50, University of Washin•lton, SeattleSeismicity and the orientation of fault planes from focal mechanisms indicate that Mount St. Helens is located at a dextral offset along the St. Helens seismic zone (SHZ): earthquake swarms occurring in this offset are related to volcanic eruptions. Because motion on the SHZ is in a right-lateral strike-slip sense, this dextral offset creates extension within a volume of the crust between the offset fault segments. This offset geometry is similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The experimental model was also used to evaluate the possible generation of instability by fault movement underneath Mayon volcano in the Philippines, a volcano that has not undergone sector collapse. Mount St. Helens is a stratovolcano that is traversed by a north-northwest right-lateral strike-slip fault that was notably active in the years before and after the 1980 collapse event (Weaver et al, 1987). Previous analog modeling showed that dome intrusion caused the collapse (Donnadieu and Merle, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental model was also used to evaluate the possible generation of instability by fault movement underneath Mayon volcano in the Philippines, a volcano that has not undergone sector collapse. Mount St. Helens is a stratovolcano that is traversed by a north-northwest right-lateral strike-slip fault that was notably active in the years before and after the 1980 collapse event (Weaver et al, 1987). Previous analog modeling showed that dome intrusion caused the collapse (Donnadieu and Merle, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As pressure decreased in the magma chamber during major explosive eruptions and then later increased as the chamber refilled, these faults failed in response to the changing radial stress field. Studies of regional seismicity [ Weaver and Smith , 1983; Shemeta and Weaver , 1986; Weaver et al , 1987] and geologic features [ Luedke and Smith , 1982; Evarts et al , 1987] suggest that a combination of NE striking volcanic lineaments and faults and a NNW trending seismic zone, the St. Helens Seismic zone (SHZ) control both the seismicity pattern and the location of the current volcanic rocks. These studies invoke right lateral motion on the SHZ in response to regional stresses and variable motion on bounding faults of a crustal spreading center under Mount St. Helens where the SHZ has an apparent dextral offset [ Weaver et al , 1987].…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains numerous examples of the localization of plutons, volcanoes, and related ore deposits in transpressional settings within arcs (e.g., Bussell, 1976;Aydin et al, 1990;Glazner, 1991;D'Lemos et al, 1992;Tikoff and Teyssier, 1992;Bellier and Sébrier, 1994;Tommasi et al, 1994;Tobisch and Cruden, 1995;Román-Berdiel et al, 1997;Acocella et al, 1999;Brown and Solar, 1999;Benn et al, 2000;García-Palomo et al, 2000;Adiyaman et al, 2001;Gleizes et al, 2001;Hildenbrand et al, 2001;Richards et al, 2001;Chernicoff et al, 2002). Additionally, numerous studies have shown how regional stress fields and resultant crustal strain influence the orientation and structure of volcanic-plutonic systems (Robson and Barr, 1964;Pollard and Muller, 1976;Nakamura, 1977;Weaver et al, 1987;Gudmundsson, 1988;Takada, 1994;Alaniz-Alvarez et al, 1998;Román-Berdiel, 1999;Mériaux and Lister, 2002).…”
Section: Tectonic Controls On Magma Ascentmentioning
confidence: 96%